KETERSEDIAAN P, SERAPAN P DAN SI OLEH TANAMAN PADI GOGO (Oryza sativa. L) PADA LAHAN ULTISOL YANG DIAPLIKASIKAN SILIKAT DAN PUPUK FOSFAT - Zulputra Zulputra; Nelvia Nelvia (Jurnal Agroteknologi, 2018)
The research was conducted from  August 2014 to Januari 2015 in the Ultisol Land, Pematang Berangan Village, Rokan Hulu Regency, Riau Province. The study aims to determine the availability of P, P and Si uptake by upland rice plants granting silicate and phosphate fertilizer on Ultisol land. The form of this research is experimental factorial completely randomized design consist of two factors. The first factor is silicate consists of four levels (0, 50, 75, and 100 kg SiO2/ha), while the second factor is phosphate fertilizer consists of four levels (0, 36, 54, and 72 kg P2O5/ha), each combination was repeated three times. The results showed that administration of silicates and phosphates increase the availability of P, P and Si uptake of upland rice crop. Giving of 100 kg SiO2 and 36 kg P2O5 per hectare increase  uptake of P and Si, each respectively increased by 208 % and 218 % compared without silicates and phosphates fertilizer.